Students' Creative Thinking in Solving Integrated Mathematical Problems Cultural Context Reviewed Based on Specialization - Indrani Eka Prastya Zahroh; Lathiful Anwar; Tjang Daniel Chandra (PRISMA, 2025)
Creativity in mathematics is essential for developing students’ problem-solving skills and innovation, yet in Indonesia, students’ creative thinking remains low, as shown by PISA and TIMSS results, indicating a significant gap between expectations and current practices in mathematics learning. To address this issue, this study aimed to analyze the creative thinking characteristics of Grade IX students when solving culturally integrated mathematical problems, while also considering differences among student specialization groups: Mathematics, Science (IPA), and Social Studies (IPS). The research employed a qualitative case study design involving 30 students from a junior high school in Malang City during the 2024/2025 academic year. Based on a creative thinking test, 15 students (6 mathematics, 5 science, and 4 social studies specialization) were selected for in-depth interviews. Data were analyzed through several stages: preparation, coding, categorization, presentation of findings, interpretation, and validation. The findings revealed distinct creative thinking characteristics across the three groups. Mathematics specialization students demonstrated strong fluency through generating many ideas, filtering logical ideas, and responding quickly; flexibility through diverse approaches and adaptability; and originality through expressing unique and innovative solutions. Science specialization students showed similar traits in fluency and flexibility, with originality evident in their ability to create and articulate unique ideas. Social studies specialization students demonstrated fluency and flexibility but lacked originality characteristics. These results highlight variations in creative thinking profiles among different specialization groups and emphasize the importance of targeted instructional strategies to foster creativity in mathematics education.